The Performance of Different Freight Wagon Bogie Types on a Small Radius Curve – Comparison of Field Measurements and Simulations - Tiia-Riikka Loponen; Rizwanullah Shaik; Riku Varis; Heikki Luomala; Pauli Kolisoja (The Baltic Journal of Road and Bridge Engineering)
The running performance of different freight wagons affects the damage they cause to the track, which in turn influences the maintenance costs of the track. The track access charges may be imposed based on the track friendliness of a wagon if the features of the wagons are known. In Finland, besides the structure of the bogies, the width of the bogies also varies since some of the bogies are designed for a track gauge of 1524 mm and some for a track gauge of 1520 mm. In this paper, the performance of different freight wagon bogies on a small radius curve is investigated by means of field measurements and simulations. Wheel-rail contact forces and angle of attack values of six different wagon types are measured. In addition, simulations are created to gain further knowledge on wheel-rail contact forces, angle of attack values, and wear values. Based on this research, it would be beneficial to use a wider track gauge in small radius curves to make the curve negotiation easier for some bogie types. It was also noticed that a small radius curve with only a short transition zone could be very risky regarding derailment potential, especially for empty wagons.